2014
DOI: 10.1111/mmi.12712
|View full text |Cite
|
Sign up to set email alerts
|

Distinct characteristics of OxyR2, a new OxyR‐type regulator, ensuring expression of Peroxiredoxin 2 detoxifying low levels of hydrogen peroxide in Vibrio vulnificus

Abstract: SummaryTwo peroxiredoxins, Prx1 and Prx2, were previously identified in Vibrio vulnificus. Besides OxyR1, a homologue of Escherichia coli OxyR (EcOxyR), OxyR2 that shares low homology with EcOxyR was first identified in V. vulnificus. OxyR2 activated prx2 during aerobic growth, while OxyR1 activated prx1 only when exposed to exogenous H2O2. OxyR2 was oxidized to form a reversible C206 to C215 disulphide bond by sensing low levels of H2O2, which were insufficient to oxidize OxyR1, and only the oxidized OxyR2 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 39 publications
4
56
0
Order By: Relevance
“…Ϫ, grown anaerobically; ϩ, grown aerobically. (22,31,48,49). This study demonstrated for the first time that IscR, rather than OxyR, activates the expression of a Prx (Prx3) (Figs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Ϫ, grown anaerobically; ϩ, grown aerobically. (22,31,48,49). This study demonstrated for the first time that IscR, rather than OxyR, activates the expression of a Prx (Prx3) (Figs.…”
Section: Discussionmentioning
confidence: 92%
“…Anerobic conditions were obtained by using an anaerobic chamber with an atmosphere of 90% N 2 , 5% CO 2 , and 5% H 2 (Coy Laboratory Products, Grass Lake, MI). For anaerobic culture, the medium was preincubated to remove resolved O 2 in the anaerobic chamber, which was verified by adding 0.00001% (w/v) resazurin salt (Sigma) to the medium as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
“…5C and D). In Vibrio vulnificus, there are two OxyR homologs, which control different peroxiredoxin genes (25). V. vulnificus OxyR2 senses H 2 O 2 with high sensitivity (26).…”
Section: Figmentioning
confidence: 99%
“…Studies of these two homologues within D. radiodurans have revealed each individually to be necessary for resistance to oxidative stress but also to function synergistically in this regard, as a mutant lacking both oxyR homologues exhibits increased sensitivity to oxidative stress (64,66). In V. vulnificus, it was found that each homologue of OxyR functioned in sensing changes in oxidation; however, each had distinct gene targets and different sensing thresholds, with one homologue responding to very low H 2 O 2 in comparison to its counterpart (65). Perhaps, in L. pneumophila, oxyR1 also interacts with the OxyR Lp regulon, adding another layer of regulatory complexity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the L. pneumophila Philadelphia genome, available on the LegioList database (http://genolist.pasteur.fr/LegioList), contains a second OxyR homologue designated oxyR1 (lpg0173). The only other organisms, to our knowledge, that contain two OxyR homologues are the Gram-positive bacterium Deinococcus radiodurans (64) and the Gram-negative pathogen Vibrio vulnificus (65). Studies of these two homologues within D. radiodurans have revealed each individually to be necessary for resistance to oxidative stress but also to function synergistically in this regard, as a mutant lacking both oxyR homologues exhibits increased sensitivity to oxidative stress (64,66).…”
Section: Discussionmentioning
confidence: 99%